IgA Nephropathy and Lupus Nephritis in a 17-Year-Old Female: A Case Report - Kimberly Sardjono; Handajaningrum, Ita Murbani (HM Publisher, 2024)
Background: Acute nephritic syndrome is classically presented with proteinuria, haematuria, azotemia, red blood casts, oliguria, and hypertension (PHARAOH) occurring acutely. Extensive inflammation of the glomeruli causes a decrease in the glomerular filtration rate so that it will produce uremic symptoms such as water and salt retention which will give a clinical picture of edema and hypertension, positive protein in the urine, the presence of erythrocytes or the appearance of dysmorphic erythrocytes in the urine. Case presentation: A 17 year old female with nephritic syndrome is reported to have nephritic lupus and IgA nephropathy. He has been treated with corticosteroids, immunosuppressants, antihypertensives, and also diuretics followed by progress of clinical and laboratory conditions. Biopsy has been performed to provide a definitive diagnosis in the patient and determine the type of nephritic syndrome experienced. The biopsy showed features of IgA nephropathy (IgAN) and lupus nephritis. Conclusion: Nephritic syndrome has been suspected due to the presence of haematuria, proteinuria, eyelid swelling, and hypertension. The management given to patients is supportive and symptomatic. Long-term administration of corticosteroids is needed in the treatment of nephritic syndrome as a maintenance therapy. Observation during treatment is needed to assess improvement or worsening of the disease experienced.